2008
DOI: 10.1161/circresaha.108.172528
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Adaptations of Coronary Microvessels Distal to a Chronic Coronary Artery Stenosis

Abstract: Abstract-Distal to a chronic coronary artery stenosis, structural remodeling of the microvasculature occurs. The microvascular functional changes distal to the stenosis have not been studied in detail. We tested the hypothesis that microvascular structural remodeling is accompanied by altered regulation of coronary vasomotor tone with increased responsiveness to endothelin-1. Vasomotor tone was studied in coronary microvessels from healthy control swine and from swine 3 to 4 months after implantation of an occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 48 publications
3
63
1
Order By: Relevance
“…In contrast, the present results are in discordance with those of the other studies. 22, 23 Sorop et al reported, using an animal model, that microvasculature distal to a chronic coronary stenosis undergoes significant functional alterations, including altered myogenic activity and increased sensitivity to ET-1. 23 A sustained state of vasoconstriction may contribute to structural microvascular modification and increased minimum microvascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the present results are in discordance with those of the other studies. 22, 23 Sorop et al reported, using an animal model, that microvasculature distal to a chronic coronary stenosis undergoes significant functional alterations, including altered myogenic activity and increased sensitivity to ET-1. 23 A sustained state of vasoconstriction may contribute to structural microvascular modification and increased minimum microvascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Since most of the abundant cytoplasmic proteins, i.e., the cytosolic and myofilamental proteins, as well as the most abundant nuclear proteins, i.e., the histones, are removed, the resulting nuclear protein extract appears to be aptly suited for further analysis of TF abundance and function. We are planning to apply this method to nuclear proteome profiling on remodeled [26] and hibernating [24] myocardium. Since there is minimal contamination of the nuclear protein extract with cytosolic proteins, this method is highly useful for the analysis of nuclear presence of TFs in different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac tissue was collected from a total of 18 Yorkshire × Landrace swine. Animals were sedated by an intramuscular injection of a mixture of ketamine and midazolam, anesthetized with intravenous pentobarbital (bolus + continuous infusion), intubated, and ventilated [24,26]. The thorax and pericardium were opened and the heart was exposed.…”
Section: Experimental Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true in light of increasing evidence that coronary microvascular dysfunction is present in a variety of coronary vascular disease states (19), with evidence of reduced NO/cGMP signaling (40) and increased ET signaling (36). Those observations have fueled the concept that microvascular dysfunction is an important component of, and contributor to, myocardial ischemia in patients with coronary artery disease (28).…”
Section: Integrated Control Of Coronary Resistance Vessel Tone In Swimentioning
confidence: 98%